Mycobacterium fortuitum abortion in a sow. (January 2022) - Cole, Allysa L.; Kirk, Natalie M.; Wang, Leyi; Hung, Chien-Che; Samuelson, Jonathan P.
Two aborted Chester White pig fetuses were presented to a veterinary diagnostic laboratory in Illinois. Postmortem examination identified no gross abnormalities. Histologic evaluation revealed multifocal necrosis of chorionic epithelial cells, coalescing areas of mineralization in the placenta, and focal accumulations of viable and degenerate neutrophils in the lung. Intra- and extracellular acid-fast bacilli were identified in the lesions in both the placenta and lungs. Bacterial culture of stomach contents yielded heavy growth of Mycobacterium fortuitum, a rapidly growing nontuberculous mycobacterium (NTM), which was further confirmed through whole-genome sequencing. NTM are opportunistic pathogens commonly found in the soil and in contaminated water supplies. In animals, M. fortuitum is typically introduced through cutaneous wounds leading to infections limited to the skin, with systemic infection being uncommon. To our knowledge, abortion caused by M. fortuitum has not been reported previously.